Extension of Mango Shelf life by Aloe vera Coating and Gene Expression - Arefin, Paroma; Amin, Ruhul; Sadiq, Md Zafar As; Dey, Subarna Sandhani; Boby, Farhana; Sarkar, Md Murshed Hasan; Habib, Md Shehan; Alam, AKM Shamsul; Parvaz, Md Shimul; Md Ibrahim (Bangladesh Journal of Nutrition, 2019)
The aloe vera based natural coatings can improve the quality and lengthen the shelf life of fruits and vegetables. In this study, the effect of mixtures of Aloe vera gel, pectin and olive oil on the improvement of quality and shelf life extension of six different cultivars of mango (Gopalbhog, Ranipochand, Khirsapat, Langra, Fazli and Aswina) have investigated. The coating of fruits (coating treated fruit) was found significantly delay the ripening process and softening of the fruit. The shelf life of coated fruits increased to 4 to 6 days compared to that of uncoated fruits. Average weight loss was 5-7% less in coated fruits compared to uncoated ones. The coated fruits showed less gene expression than uncoated one. All the above information of different mango cultivars showed variation in quality parameters. Bangladesh J. Nutr. Vol. 32, December 2019, P: 45-55